2021
DOI: 10.3390/ijerph18115939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Color Exposure on Stress, Anxiety, and Pain during Peripheral Intravenous Cannulation in Dental Patients Requiring Sedation

Abstract: Intravenous cannulation is an invasive procedure that causes stress, anxiety, and pain for many patients. A recent animal study found that exposure to green light induced antinociceptive and anxiolytic effects. This study examined whether green color exposure reduced stress, anxiety, and pain during peripheral intravenous cannulation (PIC) for sedation in dental patients. In this controlled clinical trial, 24 patients (mean age 40.9 years) were randomized to wear clear glasses or green-colored glasses for 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Previous animal and human studies 3 - 6 , 19 reported by multiple groups have confirmed the analgesic effect of GLED exposure. A cone-driven retinal pathway for migraine photophobia has been reported, in which 20% of patients exposed to green light experienced reduced pain intensity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous animal and human studies 3 - 6 , 19 reported by multiple groups have confirmed the analgesic effect of GLED exposure. A cone-driven retinal pathway for migraine photophobia has been reported, in which 20% of patients exposed to green light experienced reduced pain intensity.…”
Section: Discussionmentioning
confidence: 55%
“…18 Establishing the exact pathways through which GLED modulates pain will require ultimately further studies, as GLED-induced analgesia could also rely on the modulation of the different visual cortices. Previous animal and human studies [3][4][5][6]19 reported by multiple groups have confirmed the analgesic effect of GLED exposure. A cone-driven retinal pathway for migraine photophobia has been reported, in which 20% of patients exposed to green light experienced reduced pain intensity.…”
Section: Discussionmentioning
confidence: 56%
“…Twenty-one and sixty respondents were recruited for the preliminary and exploratory tests, respectively. The reliability coefficient was determined through a pilot test by collecting 20 (Acosta-Banda et al, 2021), 13 participants in a preliminary study (Takemura et al, 2021), and 20 to 30 subjects not included in the research samples (Bolarinwa, 2015) Based on (Tsang, Royse & Terkawi, 2017), respondent-to-item ratio advice ranged from 5:1 there were a total of sixty respondents. The inclusion criteria of this study were children aged three to six years, having their first experience of being hospitalized, receiving intravenous therapy, and not having a diagnosis of a chronic disease.…”
Section: Setting and Samplesmentioning
confidence: 99%
“…VAS-Anxiety is a standard assessment tool instead of many other VAS versions. With one question item, this instrument is reliable and valid in measuring anxiety, VAS of a computerized version (Abend et al, 2014), VAS can assess perioperative patient anxiety (Croke, 2020), as the VAS dental anxiety (Takemura et al, 2021). In another study, the validity and reliability of the Anxiety instrument found differences in the characteristics of the VAS instrument.…”
Section: Introductionmentioning
confidence: 96%
“…Virtual visiting was enabled, allowing patients to communicate with family and friends. Materials and colours were carefully chosen, with colours specifically chosen to help reduce stress and pain [ 32 , 33 ], and equipment installed outside of the line of sight of the patient as practicable, to make the space feel less clinical and overwhelming for the patient. Solutions such as a workstation on wheels and doors were included to improve patient and family privacy.…”
Section: Sound Blockingmentioning
confidence: 99%